2019
DOI: 10.1111/gcb.14737
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton decline in the eastern North Pacific transition zone associated with atmospheric blocking

Abstract: Global climate change can significantly influence oceanic phytoplankton dynamics, and thus biogeochemical cycles and marine food webs. However, associative explanations based on the correlation between chlorophyll-a concentration (Chl-a) and climatic indices is inadequate to describe the mechanism of the connection between climate change, large-scale atmospheric dynamics, and phytoplankton variability. Here, by analyzing multiple satellite observations of Chl-a and atmospheric conditions from National Center f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
5
16
0
Order By: Relevance
“…To understand the biological impacts of marine heat waves, we examine the composite of the nine simulated warm events. As expected from observations (Whitney 2015;Le et al 2019), the model simulates the greatest biological anomalies in the NPTZ, including a negative Chl anomaly (-0.03 mg m -3 , Fig. 6a) comparable with satellite 235 observations (Fig.…”
Section: Reduced Ecosystem Production and Export In Nptzsupporting
confidence: 83%
See 1 more Smart Citation
“…To understand the biological impacts of marine heat waves, we examine the composite of the nine simulated warm events. As expected from observations (Whitney 2015;Le et al 2019), the model simulates the greatest biological anomalies in the NPTZ, including a negative Chl anomaly (-0.03 mg m -3 , Fig. 6a) comparable with satellite 235 observations (Fig.…”
Section: Reduced Ecosystem Production and Export In Nptzsupporting
confidence: 83%
“…9b Previous studies have demonstrated there is a decrease in primary production in the NPTZ caused by reduced nitrate concentrations during MHWs. This decrease in nitrate concentrations was attributed to warmer upper ocean conditions, which drive a reduction in winter mixing (Amaya et al 2021), and atmospheric blocking by an atmospheric ridge (Le et al 2019), which decreases the wind-driven Ekman transport that carries nitrate from the northern Alaskan 335 gyre southward, and otherwise supports up to 40 % of the new production (Ayers and Lozier 2010). Our results agree with this literature, with both observations (Line P, Argo floats) and the MOM6-COBALT model indicating lower nitrate concentrations during MHW across the Alaskan gyre (which also has lower iron) and the NPTZ (Fig.…”
Section: Modulated Response In the Alaskan Gyrementioning
confidence: 99%
“…The problem of the mass development of phytoplankton in recent decades has become especially acute due to climate change, which can aggravate the negative consequences for the water ecosystems from human activities (e.g., Behrenfeld et al, 2006;Doney et al, 2012;Golubkov and Golubkov, 2020;Golubkov, 2021). However, the mechanisms of the eutrophication process as a result of climate change are not well understood (Le et al, 2019). The impact of climate variability on marine and estuarine ecosystem has been extensively discussed in recent decades (e.g., Stenseth et al, 2002;Doney, 2006;Doney et al, 2012;Bogatov and Fedorovskiy, 2016;Le et al, 2019;Golubkov and Golubkov, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms of the eutrophication process as a result of climate change are not well understood (Le et al, 2019). The impact of climate variability on marine and estuarine ecosystem has been extensively discussed in recent decades (e.g., Stenseth et al, 2002;Doney, 2006;Doney et al, 2012;Bogatov and Fedorovskiy, 2016;Le et al, 2019;Golubkov and Golubkov, 2020). Climate fluctuations are exogenous and hidden driving forces that are causing profound large-scale changes in marine ecosystems, affecting the state of their environment and biotic interactions on interannual and longer time scales (Andersen et al, 2011;Doney et al, 2012;Kashkooli et al, 2017;Golubkov, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation